Digestibility of dry matter and organic matter of complete rations based on banana stems in Ciayumajakuning muscovy duck - Dini widianingrum; Iwan Setiawan; Oki Imanudin; Rachmat Somanjaya (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
This study aims to obtain the digestibility of dry matter and organic matter of banana stem-based muscovy duck rations. The study was conducted experimentally using a completely randomized design (CRD) with 5 treatments and 4 replications on twenty drakes. The five treatments are P0 (ration + 0% banana stem as control), P1 (ration + 25% banana stem), P2 (ration + 50% banana stem), P3 (ration + 75% banana stem), and P4 (ration + 85% banana stem). %). Observation data were analyzed using one-way ANOVA, followed by Duncan's Multiple Range Test (DMRT) to determine differences between treatments. The results of the study showed that the Muscovy diet with the addition of 50% banana stems had the best organic matter digestibility and dry matter digestibility, namely 49.28 ± 0.23% and 54.55 ± 0.41%. It could be concluded that the Muscovy ration with the addition of 50% banana stems had the best quality.